Bringing Adam home : the abduction that changed America - Standiford, Les.; Matthews, Joe, (Detective) (New York : Ecco, 2011)
Relates the full, twenty-seven-year story behind the abduction and murder of Adam Walsh, the six-year-old son of "America's Most Wanted" host John Walsh, as well as the decades-long search for the boy's elusive killer.
Keywords: Walsh, Adam; Kidnapping -- Florida -- Case studies; Murder -- Investigation -- Florida -- Case studies